Comparative Assessment of Water Quality Parameters in Aquaculture Grow-out Using Conventional Methods And Real Time Sensors - Ajay Adarsh Rao Manupati (Dept.of Aquatic Environment Management, 2017)
Abstract- Water quality important parameters in aquaculture grow-out such as temperature, pH, salinity, ammonia, dissolved oxygen play a pivotal role and stand as the chief deciding factors that determines the fate of the culture. In the present study the water quality parameters, especially, water temperature, dissolved oxygen concentration and pH from a shrimp grow-out was analyzed using conventional methods for a period of 90 Days of Culture (DoC). There was a gradual increase in temperature as the days of culture proceeds which fluctuated from 27 from 1stDoC to to 330C at 90thDoC. Dissolved oxygen exhibited a gradual decline as the days of culture progressed and it fluctuated from 6 to 4.1 O2 mg/l; whereas, pH doesn’t exhibit wide variation and it fluctuated only between 7.6 to 7.8. The data obtained for water temperature, dissolved oxygen and pH by real time sensors exhibited perfect coherence with that of by conventional method which was cross checked at an interval of three hours. A comparative study on round the clock basis for 2 days of culture was conducted so as to unravel the efficiency of real time monitoring sensorsvis-a-vis conventional laboratory techniques with the aim of optimize the device as fault proof ones. The entire data generated out of real time sensors worked with the help of computer software named ARDUINO. The advantages of using these automated systems are that a large number of data is generated and processed in short time within minimum cost compared to the manual methods.